Understanding Ancient Moose Populations in the Southern Rocky Mountains - William T. T. Taylor; John A. F. Wendt; Jonathan Dombrosky; Crystal C'Bearing; Mikayla Costales; Isaac A. Hart; Journey LeBeau; Adrian Johnson; Elena Lompe; Russell W. Graham; Chance Ward; Emily Lena Jones; et al. (Journal of Biogeography, 2026)
Moose ( Alces alces ) are an iconic symbol of contemporary Rocky Mountain ecosystems, and their growing abundance in Colorado and other portions of the Southern Rockies has inspired debate around their regional prehistory prior to their 20th century translocation. The Early Holocene biogeography of moose in North America is poorly characterised, due in part to their life history and logistical obstacles to their archaeozoological and biomolecular identification. Even in areas where moose are well‐established today, they are often underrepresented in archaeological assemblages. Here, we assess the premodern presence of moose in the Colorado Rockies, determining that a robust historic record for moose and poor characterisation of the archaeozoological record prior to the 19th century make it scientifically inaccurate to frame moose as ‘non‐native’ within the context of contemporary management. Location Rocky Mountains, North America. Time Period Holocene (12,000 BP—present). Taxon Alces alces . Methods We conducted a review of moose sightings in historical archives (newspapers, photos, journals, and other written accounts), ethnohistoric sources (stories, songs, oral traditions), and identifications of moose in published archaeozoological assemblages from Colorado and the Southern Rockies. Results Findings reveal a clear record for premodern moose presence in the Southern Rockies stretching back to the earliest reliable written accounts, including regular presence of female and juvenile moose, pointing to local reproduction. Archaeological assemblages include a number of premodern moose identifications dating back to the Early Holocene, corroborated by the widespread reference to moose in ethnohistoric sources from Native nations in the Southern Rockies. Main Conclusions Historical and ancient data demonstrate that moose have a deep history as part of the faunal communities of the Southern Rockies, including Colorado. As rising moose populations change contemporary wildlife management choices, decision‐makers should include careful assessment of cultural and paleoecological datasets and interdisciplinary partnerships to help build effective and accurate management plans for public and private lands.

Paleoenvironments of the Late Quaternary Tonica thermokarst lake, northeastern Illinois, USA, and an extinct elk‐moose ( Cervalces ) - Russell W. Graham; Robert E. Warren; Edwin R. Hajic; Terrence J. Frest; Donald P. Schwert; Jacqueline A. Ferguson; Melissa I. Pardi; Eric C. Grimm; Frances B. King (Journal of Quaternary Science, 2026)
The Tonica Depression (TD), a late Quaternary sediment‐filled basin in northeastern Illinois, formed as a thermokarst lake as evidenced by a basal trash layer, its depositional history, and its occurrence on a late‐Pleistocene permafrost landscape. Stratigraphy and radiocarbon ages reveal that a multiproxy paleoenvironmental record extends throughout the late Wisconsin. Burning of organically enriched sediments has abbreviated the Holocene sequence. The lowest stratum is a glacial diamicton that forms the basin's floor, and at a slightly higher elevation, the rim. Lithofacies 1, supraglacial and debris flow deposits, are draped by undated Peoria Silt (PS). PS yielded molluscs and Coleoptera indicative of spruce forest ( Picea ) in a cold and harsh climate. Lithofacies 2 (ca. 17 500–18 500 cal yr BP) is a “trash zone” with white spruce ( Picea glauca ) wood, cones and needles with pollen, Coleoptera, molluscs, and vertebrates, including an elk‐moose. A “marl,” Lithofacies 3 (ca. 14 600–17 400 cal yr BP), attests to the deepening of the lake (>2 m) as also reflected by the molluscs, coleoptera, and pollen. The environment was an open spruce forest, but the climate was warmer than the previous ones. The top of this zone is composed of a brick‐red deposit with burned organic matter. Lithofacies 4 (ca. 14 600 cal yr BP) is composed of organic silt and lacustrine organic silt: a peaty silt loam. Finally, Middle Archaic artifacts on the rim of TD document human settlement around the depression during the dry and warm Middle Holocene (ca. 6747 cal BP). Tonica is the first well‐studied thermokarst lake from temperate latitudes in the United States, and it provides an excellent paleoenvironmental record of the late Pleistocene of north central Illinois.

Data augmentation in pedigreed forest tree population improves genomic prediction accuracy - Jaroslav Klápště; Mari Suontama; Emily Telfer; Natalie J. Graham; Grahame T. Stovold; Russell McKinley; Charlie Low; Heidi S. Dungey (Genetic Resources and Crop Evolution, 2026)

Cumulative environmental exposures adversely impact social behaviour and are associated with dysregulation of genes and proteins involved in epigenetic, ribosomal, and immune regulation in male mice - Morgan C. Bucknor; Brooke A. Keating; Velda X. Han; Brian S. Gloss; Pinki Dey; Nader Aryamanesh; Lee L. Marshall; Mark E. Graham; Ruwani Dissanayake; Xianzhong Lau; Shrujna Patel; Stela P. Petkova; et al. (Inflammation Research, 2026)
Objective This study investigated how cumulative environmental exposures influence offspring behaviour and inflammation-related molecular signatures in the brain and peripheral immune system. Methods A novel "triple-hit" mouse model was developed using C57Bl/6JAusB mice (N = 70), combining preconceptual social stress, antenatal high-fat diet, and a postnatal immune challenge (poly(I:C), 10 mg/kg). At 12 weeks, offspring underwent behavioural tests relevant to neurodevelopmental disorders (NDDs), including the Elevated Plus Maze, 3-Chamber Social Preference, Self-Grooming, and Marble Burying. A composite NDD-risk index was calculated. Single-cell RNA sequencing (scRNA-seq) and bulk proteomics were performed on male triple-hit offspring to identify differentially expressed genes and proteins associated with inflammatory pathways. Results Male triple-hit offspring showed elevated NDD-related behavioural risk and social deficits, not observed in females. scRNA-seq revealed altered inflammatory and ribosomal pathways in brain glia and peripheral immune cells. Proteomic analysis showed decreased abundance of proteins involved in inflammation, translation, chromatin remodelling, and synaptic function in both brain and blood. Conclusion Combined environmental stressors may drive male-specific behavioural and inflammatory changes relevant to NDDs. The identification of overlapping inflammatory signatures in brain and peripheral immune cells supports a role for shared immune mechanisms in brain–immune axis dysfunction. However, these pathway-level findings should be interpreted as preliminary hypotheses and warrant independent validation to confirm their mechanistic significance.

Selected papers of the 12th International Kimberlite Conference - Thomas Stachel; D. Graham Pearson; Sonja Aulbach; Barrett Elliott; Geoffrey H. Howarth; Kelly R. Russell; Karen V. Smit; Lutz Nasdala (Mineralogy and Petrology, 2025)

Cross-scale patterns of structure and maximum biomass in late-seral Douglas-fir-dominated rainforests - Russell D. Kramer; Stephen C. Sillett; Sean M.A. Jeronimo; Mark E. Graham; Miles E. LeFevre; Allyson L. Carroll; Robert Van Pelt (Forest Ecology and Management, 2025)

Remote sensing of electron precipitation mechanisms enabled by ELFIN mission operations and ADCS - Ethan Tsai; Akhil Palla; Austin Norris; James King; Cindy Russell; Sophie Ye; Jiashu Wu; Jason Mao; Sharvani Jha; Chanel Young; Graham Wing; Kevin Lian; et al. (Advances in Space Research, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Southern Flounder: Major Milestones and Remaining Knowledge Gaps in Their Biology, Ecology, and Fishery Management - Stephen R. Midway; Frederick S. Scharf; Michael A. Dance; Nancy J. Brown-Peterson; Joseph C. Ballenger; Nicolette S. Beeken; Russell J. Borski; Tanya L. Darden; Kenneth A. Erickson; Troy M. Farmer; Ashley Fincannon; John Godwin; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Assessing regional progress toward the sustainable development goals (SDGs): Whither the Caribbean? - Suzana N. Russell; Lila Rao-Graham; Maurice McNaughton (Environment, Development and Sustainability, 2024)

No effect of prefrontal transcranial direct current stimulation (tDCS) on food craving, food reward and subjective appetite in females displaying mild-to-moderate binge-type behaviour - Jordan D. Beaumont; Michelle Dalton; Danielle Davis; Graham Finlayson; Alexander Nowicky; Mark Russell; Martin J. Barwood (Appetite, 2023)

Linking cocoa quality attributes to its origin using geographical indications - Emily Fanning; Graham Eyres; Russell Frew; Biniam Kebede (Food Control, 2023)

Beyond purified dietary fibre supplements: Compositional variation between cell wall fibre from different plants influences human faecal microbiota activity and growth in vitro - Michael Solvang; Freda M. Farquharson; Dayan Sanhueza; Graham Horgan; Wendy R. Russell; Petra Louis (Environmental Microbiology, 2023)
Dietary fibre is a major energy source for the human gut microbiota, but it is unclear to what extent the fibre source and complexity affect microbial growth and metabolite production. Cell wall material and pectin were extracted from five different dicotyledon plant sources, apples, beet leaves, beetroots, carrots and kale, and compositional analysis revealed differences in the monosaccharide composition. Human faecal batch incubations were conducted with 14 different substrates, including the plant extracts, wheat bran and commercially available carbohydrates. Microbial activity was determined for up to 72 h by measuring gas and fermentation acid production, total bacteria (by qPCR) and microbial community composition by 16S rRNA amplicon sequencing. The more complex substrates gave rise to more microbiota variation compared with the pectins. The comparison of different plant organs showed that the leaves (beet leaf and kale) and roots (carrot and beetroot) did not give rise to similar bacterial communities. Rather, the compositional features of the plants, such as high arabinan levels in beet and high galactan levels in carrot, appear to be major predictors of bacterial enrichment on the substrates. Thus, in‐depth knowledge on dietary fibre composition should aid the design of diets focused on optimizing the microbiota.

From anecdotes to quantification: advances in characterizing volcanic eruption impacts on the built environment - Natalia Irma Deligne; Susanna F. Jenkins; Elinor S. Meredith; George T. Williams; Graham S. Leonard; Carol Stewart; Thomas M. Wilson; Sébastien Biass; Daniel M. Blake; Russell J. Blong; Costanza Bonadonna; Rodrigo Calderon B.; et al. (Bulletin of Volcanology, 2022)

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Outbreak of multi-drug-resistant (MDR) Shigella flexneri in northern Australia due to an endemic regional clone acquiring an IncFII plasmid - Christine J. D. Guglielmino; Asha Kakkanat; Brian M. Forde; Sally Rubenach; Lea Merone; Russell Stafford; Rikki M. A. Graham; Scott A. Beatson; Amy V. Jennison (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Caught in a bottleneck: Habitat loss for woolly mammoths in central North America and the ice‐free corridor during the last deglaciation - Yue Wang; Chris Widga; Russell W. Graham; Jenny L. McGuire; Warren Porter; David Wårlind; John W. Williams (Global Ecology and Biogeography, 2021)
Aim Identifying how climate change, habitat loss, and corridors interact to influence species survival or extinction is critical to understanding macro‐scale biodiversity dynamics under changing environments. In North America, the ice‐free corridor was the only major pathway for northward migration by megafaunal species during the last deglaciation. However, the timing and interplay among the late Quaternary megafaunal extinctions, climate change, habitat structure, and the opening and reforestation of the ice‐free corridor have been unclear. Location North America. Time period 15–10 ka. Major taxa studied Woolly mammoth ( Mammuthus primigenius ). Methods For central North America and the ice‐free corridor between 15 and 10 ka, we used a series of models and continental‐scale datasets to reconstruct habitat characteristics and assess habitat suitability. The models and datasets include biophysical and statistical niche models Niche Mapper and Maxent, downscaled climate simulations from CCSM3 SynTraCE, LPJ‐GUESS simulations of net primary productivity (NPP) and woody cover, and woody cover based upon fossil pollen from Neotoma. Results The ice‐free corridor may have been of limited suitability for traversal by mammoths and other grazers due to persistently low productivity by herbaceous plants and quick reforestation after opening 14 ka. Simultaneously, rapid reforestation and decreased forage productivity may have led to declining habitat suitability in central North America. This was possibly amplified by a positive feedback loop driven by reduced herbivory pressures, as mammoth population decline led to the further loss of open habitat. Main conclusions Declining habitat availability south of the Laurentide Ice Sheet and limited habitat availability in the ice‐free corridor were contributing factors in North American extinctions of woolly mammoths and other large grazers that likely operated synergistically with anthropogenic pressures. The role of habitat loss and attenuated corridor suitability for the woolly mammoth extinction reinforce the critical importance of protected habitat connectivity during changing climates, particularly for large vertebrates.

Magnesium biofortification of Italian ryegrass (Lolium multiflorum L.) via agronomy and breeding as a potential way to reduce grass tetany in grazing ruminants - Diriba B. Kumssa; J. Alan Lovatt; Neil S. Graham; Sarah Palmer; Rory Hayden; Lolita Wilson; Scott D. Young; R. Murray Lark; Beth Penrose; E. Louise Ander; Russell Thompson; Lin-Xi Jiang; et al. (Plant and Soil, 2020)
Aim Magnesium (Mg) deficiency (known as grass tetany) is a serious metabolic disorder that affects grazing ruminants. We tested whether Mg-fertiliser can increase Mg concentration of Italian ryegrasses ( Lolium multiflorum L.) including a cultivar (cv. Bb2067; ‘Magnet’), bred to accumulate larger concentrations of Mg. Methods Under controlled environment (CE) conditions, three cultivars (cv. Bb2067, cv. Bb2068, cv. RvP) were grown in low-nutrient compost at six fertiliser rates (0–1500 μM MgCl 2 .6H 2 O). Under field conditions, the three cultivars in the CE condition and cv. Alamo were grown at two sites, and four rates of MgSO 4 fertiliser application rates (0–200 kg ha −1 MgO). Multiple grass cuts were taken over two-years. Results Grass Mg concentration increased with increasing Mg-fertiliser application rates in all cultivars and conditions. Under field conditions, cv. Bb2067 had 11–73% greater grass Mg concentration and smaller forage tetany index (FTI) than other cultivars across the Mg-fertiliser application rates, sites and cuts. Grass dry matter (DM) yield of cv. Bb2067 was significantly ( p < 0.05) smaller than cv. Alamo. The effect of Mg-fertiliser rate on DM yield was not significant ( p ≥ 0.05). Conclusions Biofortification of grass with Mg through breeding and agronomy can improve the forage Mg concentration for grazing ruminants, even in high-growth spring grass conditions when hypomagnesaemia is most prevalent. Response to agronomic biofortification varied with cultivar, Mg-fertiliser rate, site and weather. The cost:benefit of these approaches and farmer acceptability, and the impact on cattle and sheep grazing on grasses biofortified with Mg requires further investigation.

Structural and Compositional Responses to Thinning over 50 Years in Moist Forest of the Northern Rocky Mountains - Chenchen Shen; Andrew S Nelson; Terrie B Jain; Meghan B Foard; Russell T Graham (Forest Science, 2019)
A thinning study was established in 1967 in moist mixed forests on the Priest River Experimental Forest in northern Idaho, USA. The study design included three thinning intensities: low, moderate, and high intensity (1,976, 988, and 494 trees ha–1). This study examined short-term (11 years) and long-term (50 years) thinning effects on residual stand characteristics, growth, and yield. Since regeneration may occur after thinning, understory change was also addressed. Thinning decreased stand density immediately but improved the growth of residual trees. Shade-tolerant species were favored in all the thinnings and dominated 50 years after thinning. Unthinned stands had higher total and merchantable volume than all thinned stands both 11 years and 50 years post treatment. Regeneration and nontree vegetation richness increased shortly after thinning, whereas nontree vegetation cover decreased sharply 50 years after treatment. The stands developed into multistrata forests with shade-tolerant species in both the overstory and understory. This is contrary to current thinning practice favoring shade-intolerant species, but demonstrates the resilience of moist Northern Rockies forests to partial overstory disturbances. In this study, thinning favoring shade-tolerant species in these mixed forests has a more significant effect on forest structure dynamics than timber production.

Conducting groundwater monitoring studies in Europe for pesticide active substances and their metabolites in the context of Regulation (EC) 1107/2009 - Anne Louise Gimsing; Jutta Agert; Nicole Baran; Arnaud Boivin; Federico Ferrari; Richard Gibson; Lisa Hammond; Florian Hegler; Russell L. Jones; Wolfram König; Jenny Kreuger; Ton van der Linden; et al. (Journal of Consumer Protection and Food Safety, 2019)

Statistical approaches to the discrimination of mantle- and crust-derived low-Cr garnets using major and trace element data - Matthew F. Hardman; D. Graham Pearson; Thomas Stachel; Russell J. Sweeney (Mineralogy and Petrology, 2018)

Mechanistic modeling of environmental drivers of woolly mammoth carrying capacity declines on St. Paul Island - Yue Wang; Warren Porter; Paul D. Mathewson; Paul A. Miller; Russell W. Graham; John W. Williams (Ecology, 2018)
On St. Paul Island, a remnant of the Bering Land Bridge, woolly mammoths persisted until 5,600 yr BP with no known predators or competitors, providing a natural system for studying hypothesized environmental drivers of extinction. These include overheating due to rising temperatures, starvation, and drought. Here, we test these hypotheses using Niche Mapper and LPJ ‐ GUESS to mechanistically estimate mammoth metabolic rates and dietary and freshwater requirements and, from these, estimate variations in island carrying capacity on St. Paul for the last 17,000 yr. Population carrying capacity may have been several hundred individuals at the time of initial isolation from the mainland. Adult mammoths could have fasted for two to three months, indicating a necessary ability to access snow‐buried forage. During the Holocene, vegetation net primary productivity increased, but shrinking island area overrode increased net primary productivity ( NPP) , lowering carrying capacity to ~100 individuals. NPP and freshwater availability alternated as critical limiting factors for this island population during the environmental changes of the late Pleistocene and Holocene. Only two or three individuals could have been sustained by the freshwater surplus in crater lakes (up to 18 individuals under the most optimistic parameter sensitivity experiments), suggesting that the St. Paul mammoth population was highly dependent on coastal freshwater sources. The simulations are consistent with the available proxy data, while highlighting the need to retrieve new paleohydrological proxy records from the coastal lagoons to test model predictions. More broadly, these findings reinforce the vulnerability of island megaherbivore populations to resource limitation and extinction.

Effects of Pollution From Anthropogenic Point Sources on the Recruitment of Sessile Estuarine Reef Biota - Amelia E. Fowles; Graham J. Edgar; Rick D. Stuart-Smith; James B. Kirkpatrick; Nicole Hill; Russell J. Thomson; Elisabeth M. A. Strain (Frontiers in Marine Science, 2018)

Memory impairment during a climbing traverse: implications for search and rescue climbing - Samantha L. Epling; Megan J. Blakely; Graham K. Edgar; Paul N. Russell; William S. Helton (Experimental Brain Research, 2018)

Mapping hot spots of breast cancer mortality in the United States: place matters for Blacks and Hispanics - Justin Xavier Moore; Kendra J. Royston; Marvin E. Langston; Russell Griffin; Bertha Hidalgo; Henry E. Wang; Graham Colditz; Tomi Akinyemiju (Cancer Causes & Control, 2018)

Translating local benthic community structure to national biogenic reef habitat types - Anna K. Cresswell; Graham J. Edgar; Rick D. Stuart‐Smith; Russell J. Thomson; Neville S. Barrett; Craig R. Johnson (Global Ecology and Biogeography, 2017)
Aim Marine reef habitats are typically defined subjectively. We provide a continental‐scale assessment of dominant reef habitats through analysis of macroalgae and sessile animal taxa at sites distributed around Australia. Relationships between reef habitats and environmental and anthropogenic factors are assessed, and potential changes in the future distribution and persistence of habitats are considered. Location Shallow rocky and coral reefs around the Australian coast. Methods Cover of 38 sessile biota functional groups was recorded in diver‐based surveys using quadrats at 1,299 sites. Classification analyses based on the functional groups were used to identify an unambiguous set of ‘biogenic habitat types’. Random forest and distance‐based linear modelling were used to investigate correlations between these habitats and environmental and anthropogenic variables. Results Cluster analyses revealed tropical and temperate ‘realms’ in benthic substratum composition, each with finer‐scale habitats: four for the temperate realm (canopy algae, barren, epiphytic algae–understorey and turf) and five for the tropical realm (coral, coral–bacterial mat, turf–coral, calcified algae–coral and foliose algae). Habitats were correlated with different sets of environmental and anthropogenic conditions, with key associations in the temperate realm between mean sea temperature and canopy‐forming algae (negative) and barren habitat (positive). Variation in sea temperature was also an important correlate in the tropical realm. Main conclusions Quantitative delineation of inshore reef habitats at a continental scale identifies many of the same habitat types traditionally recognized through subjective methods. Importantly, many biogenic reef habitats were closely related to environmental parameters and anthropogenic variables that are predicted to change. Consequently, habitats have differing likelihood of persistence. Structurally complex habitats in the temperate realm are at greater risk than more ‘two‐dimensional’ habitats (e.g., canopy‐forming versus turfing algae). In the tropical realm, offshore and coastal habitats differed greatly, highlighting the importance of large‐scale oceanic conditions in shaping biogenic structure.

Sarcoplasmic Reticulum Phospholipid Fatty Acid Composition and Sarcolipin Content in Rat Skeletal Muscle - Val Andrew Fajardo; Eric Bombardier; Khanh Tran; Adam H. Metherel; Thomas Irvine; Graham P. Holloway; Howard J. Green; Ken D. Stark; A. Russell Tupling (The Journal of Membrane Biology, 2015)

Assessing environmentally significant effects: a better strength-of-evidence than a single P value? - Graham McBride; Russell G. Cole; Ian Westbrooke; Ian Jowett (Environmental Monitoring and Assessment, 2014)

The history and dynamics of a welded pyroclastic dam and its failure - Graham D. M. Andrews; James K. Russell; Martin L. Stewart (Bulletin of Volcanology, 2014)

Synchronizing feather-based measures of corticosterone and carotenoid-dependent signals: what relationships do we expect? - Graham D. Fairhurst; Russell D. Dawson; Harry van Oort; Gary R. Bortolotti (Oecologia, 2014)

Ancient DNA supports southern survival of R ichardson's collared lemming ( D icrostonyx richardsoni ) during the last glacial maximum - Tara L. Fulton; Ryan W. Norris; Russell W. Graham; Holmes A. Semken; Beth Shapiro (Molecular Ecology, 2013)
Collared lemmings (genus D icrostonyx ) are circumpolar A rctic arvicoline rodents associated with tundra. However, during the last glacial maximum ( LGM ), D icrostonyx lived along the southern ice margin of the L aurentide ice sheet in communities comprising both temperate and boreal species. To better understand these communities and the fate of these southern individuals, we compare mitochondrial cytochrome b sequence data from three LGM ‐age D icrostonyx fossils from south of the L aurentide ice sheet to sequences from modern Dicrostonyx sampled from across their present‐day range. We test whether the D icrostonyx populations from LGM ‐age continental USA became extinct at the P leistocene– H olocene transition ~11000 years ago or, alternatively, if they belong to an extant species whose habitat preferences can be used to infer the palaeoclimate along the glacial margin. Our results indicate that LGM ‐age D icrostonyx from I owa and S outh D akota belong to D icrostonyx richardsoni , which currently lives in a temperate tundra environment west of Hudson Bay, Canada. This suggests a palaeoclimate south of the Laurentide ice sheet that contains elements similar to the more temperate shrub tundra characteristic of extant D . richardsoni habitat, rather than the very cold, dry tundra of the N orthern A rctic. While more data are required to determine whether or not the LGM southern population is ancestral to extant D . richardsoni , it seems most probable that the species survived the LGM in a southern refugium.

Requirements for labelling forest polygons in an object-based image analysis classification - Meghan Graham MacLean; Michael J. Campbell; Daniel S. Maynard; Mark J. Ducey; Russell G. Congalton (International Journal of Remote Sensing, 2013)

The effectiveness of cloning for the genetic improvement of Mexican white cypress Cupressus lusitanica (Mill.) - Heidi S. Dungey; John H. Russell; João Costa e Silva; Charlie B. Low; Mark A. Miller; Kane R. Fleet; Graham T. Stovold (Tree Genetics & Genomes, 2013)

Differential retinal origins of separate anatomical channels for pattern and motion vision in rabbit - I. Steele-Russell; M. I. Russell; J. A. Castiglioni; J. Graham (Experimental Brain Research, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Silviculture and Forest Ecology - David Mercker; Ryan Blair; Don Tyler; Theresa Jain; Russell Graham; Donald Rockwood; Nicholas Koch; Jeremy Brawner; Omar Carrero; Kristofer Covey; Alex Barrett; Mark Ashton; et al. (Journal of Forestry, 2011)
2Over the past several decades, federal incentive programs have encouraged the restoration of bottomland forests throughout the West Gulf Coastal Plain (WGCP) and the Lower Mississippi Alluvial Valley (LMAV). Programs such as the Conservation Reserve (CRP) and Wetlands Reserve (WRP) Programs have been marginally successful (Stanturf et al. 2001). Foresters and contractors often follow conventional tree planting procedures that are well established for upland sites, but prove problematic in bottomlands. High water tables, soil drainage and compaction, overland flooding and diverse soil properties make species selection difficult. Slight changes in topography and soil structure often have a dramatic effect on survival and growth of planted oak seedlings (Hodges and Schweitzer 1979). This project documented the survival and growth of six-year old seedlings that were established on a bottomland site in 2004, located at the West Tennessee Research and Education Center, Jackson, Tennessee. The purpose was to determine how soil drainage as indicated by mottling (specifically, the point of 50 percent gray color throughout the soil profile) affects the survival and growth of bottomland oak species. The findings suggest that practitioners plant Nuttall, pin and overcup oaks in poorly drained soils. As the drainage improves, begin mixing in willow oak. In the best drained soils (if they exist), finish by including water, swamp chestnut, swamp white, Shumard, cherrybark and bur oaks. Potential species diversity should expand as the soil drainage improves.

Estimating carbon in savanna ecosystems: rational distribution of effort - Russell M. Wise; Graham P. von Maltitz; Robert J. Scholes; Chris Elphinstone; Renee Koen (Mitigation and Adaptation Strategies for Global Change, 2009)

Decomposition and macroinvertebrates in experimental litter along a secondary chronosequence of tropical montane forest - Simoneta Negrete-Yankelevich; Carlos Fragoso; Adrian C. Newton; Graham Russell; O. William Heal (Biology and Fertility of Soils, 2008)

Species-specific characteristics of trees can determine the litter macroinvertebrate community and decomposition process below their canopies - Simoneta Negrete-Yankelevich; Carlos Fragoso; Adrian C. Newton; Graham Russell; O. William Heal (Plant and Soil, 2008)

Science Information for Informing Forest Fuel Management in the Dry Forests of the Western United States - Sarah McCaffrey; Russell Graham (Journal of Forestry, 2007)
Land managers need timely and straightforward access to the best scientific information available for informing decisions on how to treat forest fuels in the dry forests of the western United States. However, although there is a tremendous amount of information available for informing fuels management decisions, often, it is in a form that is difficult to use or of limited applicability. To improve access, interpretability, and use of the full body of research, a pilot project was initiated by the USDA Forest Service to synthesize relevant scientific information and develop publications and decisions support tools that managers can use to inform fuels treatment plans. This article provides an overview of the project and briefly discusses key lessons learned as an introduction to a series of articles, to be published in future Journal of Forestry issues, on different topic areas addressed by the project.

Spatial Patchiness of Litter, Nutrients and Macroinvertebrates during Secondary Succession in a Tropical Montane Cloud Forest in Mexico - Simoneta Negrete Yankelevich; Carlos Fragoso; Adrian C. Newton; Graham Russell; O. William Heal (Plant and Soil, 2006)

An assessment of European pig diversity using molecular markers: Partitioning of diversity among breeds - Louis Ollivier; Lawrence Alderson; Gustavo C. Gandini; Jean-Louis Foulley; Chris S. Haley; Ruth Joosten; Annemieke P. Rattink; Barbara Harlizius; Martien A. M. Groenen; Yves Amigues; Marie-Yvonne Boscher; Geraldine Russell; et al. (Conservation Genetics, 2005)

An Integrated Ecosystem Assessment of the Interior Columbia Basin - Russell T. Graham; Thomas M. Quigley; Rebecca Gravenmier (Environmental Monitoring and Assessment, 2000)

The effect of suramin on the resorption of bovine nasal cartilage - Claire L. Lewis; Astrid Frazer; R. Graham G. Russell; Rowena A. D. Bunning (Inflammopharmacology, 1999)

Cardiovascular disease in the JCR:LA-cp rat - James C. Russell; Sandra E. Graham; Mary Richardson (Molecular and Cellular Biochemistry, 1998)

A Framework for Ecosystem Management in the Interior Columbia Basin - Richard W. Haynes; Russell T. Graham; Thomas M. Quigley (Journal of Forestry, 1998)
A framework was developed to set forth the relationship of science to management for the Interior Columbia Basin Ecosystem Management Project. It incorporates a general planning model that has four iterative steps: monitoring, assessment, decisionmaking, and implementation. In this effort we recognized that people are part of ecosystems and that stewardship must resolve the challenge of how to meet multiple demands with finite resources. Science helps decisionmakers choose among options for dynamic systems, but the real challenge is determining whose values will influence land management.

Inhibition of Growth of Dictyostelium discoideum Amoebae by Bisphosphonate Drugs Is Dependent on Cellular Uptake - Michael J. Rogers; Xiaojuan Xiong; Xiaohui Ji; Jukka Mönkkönen; R. Graham G. Russell; Michael P. Williamson; Frank H. Ebetino; Donald J. Watts (Pharmaceutical Research, 1997)

Site preparation alters soil distribution of roots and ectomycorrhizae on outplanted western white pine and Douglas-fir - Alan E. Harvey; Deborah S. Page-Dumroese; Martin F. Jurgensen; Russell T. Graham; Jonalea R. Tonn (Plant and Soil, 1997)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)